The Effect of Diabetes Mellitus on Mortality in Patients Hospitalized Intensive Care Unit in Covid-19 Pandemic - Balta Başı, Nermin; Metin, Seyhan; Acar Sevinç, Sultan; Peker, Nebia; Çınar, Ayşe Surhan; Salkaya, Aysel; Altuntaş, Yüksel; Özdemir, Hacı Mustafa (Acta Biomedica Atenei Parmensis, 2022)
Backgorund and aim: There are many studies on the effects of Diabetes Mellitus on the clinical course in COVID-19 patients. Factors that increase the risk of contracting COVID-19 disease and increase disease progression have been caused, and diabetes mellitus is one of them. We aimed to evaluate the incidence of Diabetes Mellitus in patients treated in the intensive care unit in respiratory failure due to COVID-19 pneumonia, and the effect of Diabetes Mellitus on the length of stay in intensive care and mortality.Methods: Our study is a single-center retrospective study. The study includes patients hospitalized in our COVID intensive care unit between March 16, 2019, and May 16, 2020 Patients over 18 years of age with and without a history of Diabetes Mellitus were compared in 2 groups. Demographic data of the patients, length of stay in the intensive care unit, respiratory support methods, presence of other comorbid diseases, effects of Diabetes Mellitus to mortality in ICU were recorded.Results: The information of 150 patients was obtained in the COVID-19 intensive care units of our hospital. Diabetes Mellitus was detected in 49 of the patients hospitalized in intensive care. 34.7% of these patients were female and 65.3% were male. There was no significant difference in survival in both groups (p = 0.942). The BMI of the patients with Diabetes Mellitus was 27.07 ± 2.55, significantly higher (p = 0.005). Intensive care stay periods were similar in both groups. The presence of hypertension was significantly higher in those with Diabetes Mellitus (p = 0.000). There was no statistically significant difference between respiratory support methods.Conclusions: Diabetes Mellitus did not affect the duration of stay in the intensive care unit and mortality in patients who were followed up and treated in the intensive care unit due to COVID-19 pneumonia.